Studi Kurikulum Pembelajara Pendidikan Gender Pada Lembaga Pendidikan Islam (studi kasus di SD Alam Arrohmah Putri Hidayatullah Malang) - Nanik, Suhar (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2013)
The gender understanding is determined by the understanding for everyeach of men and woman that based on space and time. The period in which a people in an order based education elementary school of Islam into a futurethat can impact one’s mindset so that later in life will become an adult who has the perspective of gender with various categories of space and time. The education elementary school will guide for people become an distinguish men and woman right into place. Comprehensive accuracy in distinguishing men in woman are create a harmony in life. Harmony in life became an ideallife that should be built by joined between men and woman as the same. It all make them fulfil their needed and survival. This research was carried out by using a riew of the curriculum in education elementary school of Islam and study was done to prove that fially there is no curriculum that introduced for gender. There is no mention to illustrate and to explain of the differences between men and woman by socio and cultural. This understanding is very important in education elementary school of Islam for child mentally physical changes. The result of this research indicatedby the fact and document that there is no signifiant curriculum clearly implied that talking about gender.Keywords: Gender, Curriculum, Elementary School.